A Systemic Functional Linguistic Study on Language Use of Indonesian Students in Writing - Yuzaki Adam Alwasilah; Gunawan, Wawan (JOMANTARA, 2023)
Language is a form of cultural wealth of a nation. Analysis of the use of a language is an interesting topic to study. The current manuscript implement Systemic functional linguistics (SFL) theory which focuses on exploring the social and cultural context of language use in a piece of writing. SFL it self is an approach to linguistics that considers language as a social semiotic system  which focuses on the function of language in social contexts and the choices that language users make. This paper is intended to analyze students’ recount text writing in SFL perspectives, and how teachers can assist students in solving writing problems. Specifically this study hopefully can identify in what aspects that Indonesian students usually made some errors, based on three metafunctions from SFL perspective. The finding shows that most of the students did errors in the use of tense, generic structure, and grammatical errors. Thus, Transition-Action-Details (TAD) could be used as one of the strategies in teaching writing, especially writing recount text in Indonesian context.